FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI BERWIRAUSAHA KARYAWAN HOTEL KECAMATAN KUTA SELATAN - Rumapea, Ralen Rouli Agustina; Piartrini, Putu Saroyini (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022, 2022)
Entrepreneurial intention is a person's motivation to create new and innovative business activities through their abilities. Initial research results based on interviews with 4 hotel employees in South Kuta District who were laid off during the Covid-19 pandemic stated that they did not have a business idea, were unsure of their own abilities in entrepreneurship, and were not interested in a career as an entrepreneur. This research was conducted on hotel employees in South Kuta District who were laid off during the Covid-19 pandemic, which consisted of 82 men and 51 women, most of whom were aged 26-31 years, had a final D3 education, the field of science studied, namely tourism, and had a bachelor's degree in tourism. 1-4 years of service. The number of samples in this study were 133 respondents. The sampling technique is non-probability sampling. Data collection was obtained from the results of distributing questionnaires directly and online to respondents using google form. Data analysis in this study used multiple linear regression analysis. The results of this study indicate that attitude towards entrepreneurship, subjective norms and perceived behavioral control have a positive and significant effect on respondents' entrepreneurial intentions.